2020
DOI: 10.5194/egusphere-egu2020-11550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Evolution and Role of Solar Wind Turbulence in the Inner Heliosphere

Abstract: The first two orbits of the Parker Solar Probe (PSP) spacecraft have enabled the first in situ measurements of the solar wind down to a heliocentric distance of 0.17 au (or 36 R ⊙ ). Here, we present an analysis of this data to study solar wind turbulence at 0.17 au and its evolution out to 1 au. While many features remain similar, key differences at 0.17 au include: increased turbulence energy levels by more than an order of magnitude, a magnetic field spectral index of −3/2 matching that of the velocity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 105 publications
5
31
1
Order By: Relevance
“…On the other hand, at intermediate scales (say the inertial range), the radial evolution suggests a transition from a Kraichnan‐like scaling of the power density toward a Kolmogorov‐like scaling when the heliocentric distance increases. This feature is in agreement with recent studies of the radial evolution of solar wind turbulence limited to PSP data (Chen et al., 2020; Duan et al., 2020). The same transition is recovered in the power spectrum of velocity fluctuations (not shown) but spread over a larger range of distances.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, at intermediate scales (say the inertial range), the radial evolution suggests a transition from a Kraichnan‐like scaling of the power density toward a Kolmogorov‐like scaling when the heliocentric distance increases. This feature is in agreement with recent studies of the radial evolution of solar wind turbulence limited to PSP data (Chen et al., 2020; Duan et al., 2020). The same transition is recovered in the power spectrum of velocity fluctuations (not shown) but spread over a larger range of distances.…”
Section: Discussionsupporting
confidence: 93%
“…Chen et al. (2020) observed an increased turbulence energy level by more than an order of magnitude and a lower magnetic compressibility compared to the plasma measured at 1 AU. Moreover, in the inertial range of the turbulent cascade, they found for the Alfvénic slow stream a typical spectral index of about −3/2 for both magnetic and velocity fields and a dominance of outward‐propagating Alfvénic fluctuations with respect to the inward‐propagating ones.…”
Section: In Situ Observationsmentioning
confidence: 92%
“…Note that the much lower power at 50 solar radii is evidence that the electric field noise floor is a few orders of magnitude below the data at perihelion. A study of the radial dependence of Alfvenic turbulence in magnetic field data below 1 Hz has also been made (Chen et al, 2020), but this study did not discuss the >1‐Hz frequencies found in this work.…”
Section: The Electric Field Power Spectrummentioning
confidence: 82%
“…In general, even when the physical process at work in the creation of the PSD is well known, any individual instances may not produce a fully developed PSD of that type, so the flexibility provided by our algorithm may still be needed. For example, the PSD spectral slope of the solar wind parameters in the inertial range evolves with increasing distance from the Sun, steepening from −3/2 to −5/3 for the velocity (Roberts, 2010) and magnetic field (Chen et al., 2020), or may tend toward −2 in the presence of discontinuities (Roberts, 2010) or anisotropies (Horbury et al., 2012). We use the statistical properties of the adaptive MTM to develop a maximum likelihood determination of the PSD background as in Vaughan (2010).…”
Section: Discussionmentioning
confidence: 99%